Pola Perilaku Pencegahan KTD dan Penularan IMS pada Anak Jalanan di Kota Semarang - Shofa, Ikhwanush; Shaluhiyah, Zahroh; Husodo, Besar Tirto; Musthofa, Syamsulhuda Budi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
Street children are children under the age of 18 who spend most of their time living on the streets or other public places. The lack of supervision and education of street children, especially at the age of teenagers, makes street children have a high risk of premarital sex. Premarital sex is a major risk factor for unwanted pregnancies and the transmission of sexually transmitted infections. This study aims to determine how the behavior of street children in the city of Semarang in avoiding the impact of premarital sex behavior. This study uses a descriptive method with a qualitative approach with the technique of taking research subjects using a questionnaire. The research subjects were 2 street children who were female and had had premarital sex. Triangulation research subjects were 2 people who were parents and caregivers of the research subjects. The research data was taken by in-depth interview technique. The results showed that the behavior of Unwanted Pregancies and STI prevention of research subjects was still poor. Both study subjects had experienced unwanted pregnancies. They never seek information about the impact of premarital sex and how to prevent it. They also never had a health professional consultation with health workers. To prevent contracting STIs, they are only being careful in choosing sex partner, choosing to be loyal to their boyfriend, or using condoms. To prevent pregnancy they use condoms or, preferably, interrupted intercourse. Unfortunately, these prevention technique was not carried out properly, causing the research subjects to experience unwanted pregnancies.